The resilience among suicide attempt survivor - Fatwa Tentama; Tri Wahyuni Sukesi; Surahma Asti Mulasari; Sulistyawati Sulistyawati (International Journal of Public Health Science (IJPHS), 2020)
Suicide incidents in Gunungkidul, Indonesia have increased from year by year. This phenomenon is of great importance to study to find a proper solution. Based on the data it has been found that people who have committed suicide but have been saved (survived). To date, they have managed to survive and carry out their daily activities well. The majority of suicide attempts are caused by unpleasant experiences in the past. The purpose of this study was to assess the resilience of suicide survivors who can be used to motivate people who intend or who survived suicide to get back up. This research used a qualitative approach with a phenomenological method. The location of this research was in Gunungkidul Regency. The subjects of this study were four people who were obtained by using purposive sampling technique. Several in-depth interviews were carried out to collect the data from the respondent.  The results show that the factors supporting the resilience of survivors to suicide were the ability to control emotions and impulses, self-efficacy and optimism, the ability to analyze the causes of problems, empathy, and the ability to achieve what was desired.